2003
DOI: 10.1007/s00221-003-1498-1
|View full text |Cite
|
Sign up to set email alerts
|

Representation of heading direction in far and near head space

Abstract: Manipulation of objects around the head requires an accurate and stable internal representation of their locations in space, also during movements such as that of the eye or head. For far space, the representation of visual stimuli for goal-directed arm movements relies on retinal updating, if eye movements are involved. Recent neurophysiological studies led us to infer that a transformation of visual space from retinocentric to a head-centric representation may be involved for visual objects in close proximit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
4
7
0
Order By: Relevance
“…We assessed to what extent interception errors depend on the initial and final eccentricities of the interception point relative to gaze in a spatial updating paradigm, in which a saccade is made between viewing and reaching toward a moving target. In a control task involving stationary targets, we replicated the previous findings (i.e., gaze-centered overshoots and updating; Baker, Harper, & Snyder, 2003;Henriques et al, 1998;Medendorp & Crawford, 2002;Poljac & van den Berg, 2003;Pouget et al, 2002;Sorrento & Henriques, 2008;Van Pelt & Medendorp, 2007; see Supplementary material). Similar but more variable effects occurred for interception.…”
Section: Discussionsupporting
confidence: 84%
“…We assessed to what extent interception errors depend on the initial and final eccentricities of the interception point relative to gaze in a spatial updating paradigm, in which a saccade is made between viewing and reaching toward a moving target. In a control task involving stationary targets, we replicated the previous findings (i.e., gaze-centered overshoots and updating; Baker, Harper, & Snyder, 2003;Henriques et al, 1998;Medendorp & Crawford, 2002;Poljac & van den Berg, 2003;Pouget et al, 2002;Sorrento & Henriques, 2008;Van Pelt & Medendorp, 2007; see Supplementary material). Similar but more variable effects occurred for interception.…”
Section: Discussionsupporting
confidence: 84%
“…This bias effect in accuracy most likely reflects an influence of the experimental configuration, in which the targets were aligned horizontally with the fixation location. As observed in previous studies (Bock, 1986;Henriques et al, 1998;Henriques and Crawford, 2000;Medendorp and Crawford, 2002;Pouget et al, 2002;Poljac and Van Den Berg, 2003), baseline horizontal errors for reaches to peripheral targets are biased relative to gaze-position angle; therefore, any rTMS-induced errors reported here are relative to these baseline errors (supplemental Fig. S1, available at www.jneurosci.org as supplemental material).…”
Section: Saccade and Reach Accuracysupporting
confidence: 61%
“…Thus, the retinal flow limitation on the precision of heading perception points to a retinal position reference of head-centric flow signals. This conclusion is supported by a recent study by (Poljac & van den Berg, 2003). They found that pointing towards memorized perceived heading direction showed the same type of retino-centric errors following a saccadic eye movement as pointing towards single LED targets.…”
Section: Perception In a Mixed Reference Framesupporting
confidence: 80%